Intrapopulational genetic differentiation in Anopheles (N.) darlingi root, 1926 (Diptera: Culicidae) in the Amazon Region - Santos, Joselita Maria Mendes dos (1999)
Four natural Amazonian Anopheles darlingi populations were analyzed for 19 loci, 12 of which showed variation, i.e., 68.4% of polymorphic loci. The Ariquemes, Rondonia, population was the most variable, with a large number of alleles per locus (2.26 ± 0.27) and high polymorphism (P = 63.15). The highest values of observed and expected intralocus heterozygosity were observed in the Manaus, Amazonas, population (Ho = 0.432 ± 0.11; He = 0.375 ± 0.08), and the lowest in the Cachoeira Porteira, Para, population (Ho = 0.236 ± 0.09; He = 0.290 ± 0.11). Wright's F-statistic revealed disequilibrium caused by an excess of homozygotes, as shown by the F(is) > F(st) values (F(is) = 0.083 > 0.026) reflecting intrapopulational differentiation. The four populations studied were genetically similar, as indicated by distance and similarity values. Chromosomal variation of Amazon population also did not indicate geographical differentiation, and populations in the central region of the Amazon Basin showed high polymorphism in relation to the marginal populations, which were mainly monomorphic.